Pembuatan Model Regresi Linear Berganda pada Saham PT Bank Negara Indonesia Tbk dalam Bursa Efek Indonesia - Al Azizu, khairannisa; Rosita, Silvia; narwen, Narwen (Program Studi Aktuaria, Fakultas Sains Teknologi dan Pendidikan, Universitas Tamansiswa Padang, 2025)
This study aims to develop a multiple linear regression model to predict the closing price of PT Bank Negara Indonesia Tbk (BNI) shares listed on the Indonesia Stock Exchange (IDX). The independent variables used include the opening price, high price, low price, and trading volume. Historical data on BNI shares over a specific period were analyzed to identify the influence of each variable on the closing price. Classical assumption tests were conducted, including normality, heteroscedasticity, and autocorrelation tests, to ensure the validity of the regression model. The results show that some independent variables have a significant influence on the closing price, with stable and reliable regression coefficients. The resulting regression model is expected to serve as a decision-making tool for BNI stock investments on the Indonesia Stock Exchange.